The Study Of Susceptibility And Cytokine Production In Dengue Virus Type 2 (Denv2)-Infected Monocytes Of Individuals With Glucose-6-Phosphate Dehydrogenase (G6pd) Deficiency - Al-Alimi, Abdullah Abdull Jabbar Ahmed (2013)
Dengue virus is endemic in peninsular Malaysia. The clinical manifestations vary depending on the incubation period of the virus as well as the immunity of the patients. Glucose-6-phosphate dehydrogenase (G6PD) deficiency is prevalent in Malaysia, where the incidence is 5.2%. It has been noted that G6PD-deficient individuals suffer from more severe clinical presentation of dengue infection. The aim of this study is to investigate the susceptibility of monocytes to DENV2 infection, the oxidative responses, and cytokine production in monocytes from G6PD-deficient individuals. Blood samples were collected from donors after being approved by the Research Ethical Committees of USM and Ministry of Health. Screening for G6PD was performed using the florescent spot method followed by the quantitative assay. Monocytes from G6PD-deficient and healthy individuals (G6PD-normal) were isolated and infected with DENV2, whereby multiplicity of infection (MOI) 0.1 and intracellular infection rate were measured by flow cytometry and extracellular by plaque assay. Levels of oxidative species, superoxide anions (O2•-), nitric oxide (NO), oxidative stress and cytokines were determined and compared with normal controls.